Interaction of bacteria and male reproductive system blackening disease of captive Penaeus setiferus - Alfaro-Montoya, Jorge (1993)
The genital apparatus of male penaeid shrimp, Penaeus sett’ferus, blackens with resulting detrimen tal effects ton mating for production of larvae when animals are kept in controlled maturation/repro duction situations. A progressive, melanized condition of the male reproductive tract was shown to be associated with bacterial infection. At least three different species ( Vibrio alginolyticus, Pseudo monas putrefaciens, and an unclassified strain), were isolated from damaged tissues and successfully developed the same signs in challenge experiments. It is suggested that the condition could be a pro gressive syndrome with bacterial invasion perhaps only in the advanced stages, or that more than one etiology may be involved in deterioration and blackening of the P. setiferus reproductive system.